Gambaran Gaya Hidup Hedonisme pada Remaja di SMA X Surabaya - Samda Awalia Azzahra; Prianggi Amelasasih; Haniwati Haniwati (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
A hedonistic lifestyle is a person's lifestyle as a process of using the money and time they have which is expressed in activities, interests and opinions. Therefore, researchers want to know more deeply about the description of the hedonistic lifestyle in teenagers. The aim of this research is to provide an overview of the hedonistic lifestyle of teenagers at SMA X Surabaya. This type of research uses qualitative research methods with a case study approach. Case study is a type of qualitative research, where the author conducts an in-depth exploration of programs, events, processes, activities of individuals related by time and activity. Data collection was carried out using interviews and observations carried out on the three subjects with significant others. Based on the results of the analysis from this research, the three subjects experienced a hedonistic lifestyle in accordance with aspects of the hedonistic lifestyle. The activity aspect of the three subjects was spending time outside the home, such as gathering in cafes, walking to the mall. In terms of interest, the three subjects really like shopping for clothes, shoes and bags. The three subjects also really liked branded goods when shopping. Then in the third opinion aspect, the subject really likes trendy items to seek material enjoyment as the main goal in life. The factors that influence a hedonistic lifestyle are internal and external factors that influence a hedonistic lifestyle in teenagers, namely from the environment to the family which supports the three subjects in a hedonistic lifestyle.